Global Health Partnerships and the Brocher Declaration: Principles for Ethical Short-Term Engagements in Global Health. Issue 1 (17th May 2022) - Prasad, Shailendra; Aldrink, Myron; Compton, Bruce; Lasker, Judy; Donkor, Peter; Weakliam, David; Rowthorn, Virginia; Mantey, Efua; Martin, Keith; Omaswa, Francis; Benzian, Habib; Calgua-Guerra, Erwin; et al.
Short- term experiences in global health (STEGH), also known as short-term medical missions continue to be a popular mode of engagement in global health activities for students, healthcare providers, and religious groups, driven primarily by organizations from high-income countries. While STEGH have the potential to be beneficial, a large proportion of these do not sustainably benefit the communities they intend to serve, may undermine local health systems, operate without appropriate licenses, go beyond their intended purposes, and may cause harm to patients. With heightened calls to "decolonize" global health, and to achieve ethical, sustainable, and practical engagements, there is a need to establish strong guiding principles for global health engagements. The Advocacy for Global Health Partnerships (AGHP), a multi-sectoral coalition, was established to reflect on and address the concerns relating to STEGH. Towards this end, AGHP created the Brocher Declaration to lay out six main principles that should guide ethical and appropriate STEGH practices. A variety of organizations have accepted the Declaration and are using it to provide guidance for effective implementation of appropriate global health efforts. The Declaration joins broader efforts to promote equity in global health and a critical reevaluation of volunteer-centric, charity-based missions. The current state of the world's health demands a new model of collaboration – one that sparks deep discussions of shared innovation and builds ethical partnerships to address pressing issues in global health.